Leaf polyphenol profile and SSR-based fingerprinting of new segregant Cynara cardunculus genotypes - Pandino, Gaetano; Lombardo, Sara; Moglia, Andrea; Portis, Ezio; Lanteri, Sergio; Mauromicale, Giovanni (Frontiers in Plant Science, 2015)
The dietary value of many plant polyphenols lies in the protection given against degenerative pathologies. Their in planta role is associated with the host's defence response against biotic and abiotic stress. The polyphenol content of a given plant tissue is strongly influenced by the growing environment, but is also genetically determined. Plants belonging to the Cynara cardunculus species (globe artichoke and the cultivated and wild cardoon) accumulate substantial quantities of polyphenols (mainly mono and di-caffeoylquinic acid (CQA) in their foliage. Transgressive segregation for CQA content in an F1 population bred from a cross between a globe artichoke and a cultivated cardoon led to the selection of eight segregants which accumulated more CQA in their leaves than did those of either of their parental lines. The selections were grown over two seasons to assess their polyphenol profile (CQAs, apigenin and luteolin derivatives and narirutin), and were also fingerprinted using a set of 217 microsatellite markers. The growing environment exerted a strong effect on polyphenol content, but two of the selections were able to accumulate up to an order of magnitude more CQA than either parent in both growing seasons. Since the species is readily vegetatively propagable, such genotypes can be straightforwardly exploited as a source of pharmaceutically valuable compounds, while their SSR-based fingerprinting will allow the genetic identity of clonally propagated material to be easily verified.